Teachers’ perception on the role of social interaction among special needs in preschool - Ramakrishnan, Revati (Jurnal Pendidikan Bitara UPSI, 2019)
Special education is a field which is growing, commanding more attention in the recent years. There have been more children over the past decade who have been diagnosed with special needs. There have been schools which provide education specifically for children with special needs for many years. In the recent years regular preschools have started to cater for children with special needs. This research mainly looks at if teachers think social interaction can be used as a tool to enhance cognitive development and on how can social interaction be used as a tool to enhance the cognitive development of children with special needs. 25 teachers who work with special needs children within Klang Valley were interviewed. An interview questionnaire that consists of 14 questions was prepared. Results showed that social interaction can be used as a tool to enhance the cognitive development of children with special needs, however there are many factors involved in achieving this.